2022
DOI: 10.31351/vol30isssuppl.pp31-39
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Beliefs to Adjuvant Hormonal Therapy in Patients with Breast Cancer: A Cross-Sectional Study (Conference Paper) #

Abstract: Breast cancer is the most common cancer among women over the world. To reducing reoccurrence and mortality rates, adjuvant hormonal therapy (AHT) is used for a long period. The major barrier to the effectiveness of the treatment is adherence. Adherence to medicines among patients is challenging. Patient beliefs in medications can be positively or negatively correlated to adherence. Objectives: To investigate the extent of adherence and factors affecting adherence, as well as to investigate the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The goal of this study is to assess knowledge and rate of adherence to supplement medications among pregnant women in Iraq; especially after several studies showed that patients' adherence to different medication is less than required. [18][19][20]…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this study is to assess knowledge and rate of adherence to supplement medications among pregnant women in Iraq; especially after several studies showed that patients' adherence to different medication is less than required. [18][19][20]…”
Section: Introductionmentioning
confidence: 99%
“…At number five on the list of common causes of cancer-related fatalities, About 500,000 people die from breast cancer every year in the world [5]. Among them, the number and mortality rate of women diagnosed with breast cancer rank second among all cancers [6,7].…”
Section: Introductionmentioning
confidence: 99%